Characterization of Protomyces macrosporus causing stem gall of coriander (Coriandrum sativum) - LEHARWAN, MUNISH; GUPTA, MEENU; CHAUHAN, ANJALI; SHUKLA, ARTI; KUMAR, UTTAM (The Indian Journal of Agricultural Sciences, 2021)
Coriander (Coriandrum sativum L.) is an annual herbaceous plant and suffers from different fungal, bacterial andviral diseases of which stem gall caused by Protomyces macrospores is one among them. The disease appears in theform of tumour like swellings of leaf veins, leaf stalks, peduncles, stems and on fruits. The test pathogen was isolatedfrom infected stem and seeds and pure culture of the fungus was obtained on potato dextrose agar enriched with yeastextract medium. The colour of colony was creamy white initially which later turned light brown. Morphologicalcharacters comprising chlamydospores were studied which were yellowish brown, spherical or globose to oval,single-celled, smooth and measured 40-80 Î¼ in diameter. For molecular characterization, genomic DNA was isolatedusing standard procedures and a region of the nuclear rDNA gene containing the internal transcribed spacer regionswas amplified from the genomic DNA. Phylogenetic tree showed that isolated strain A clustered close to Protomycesinouyei with 62% similarity only. Based on morphological characteristics, the isolated fungus was identified asProtomyces macrosporus but on the ITS sequences comparisons, strain A was similar to Protomyces sp. Pathogenicitytests showed that crushed powder of infected seed added to soil was better in disease development over mycelialsuspension and the symptoms of the disease appeared in 42.5 days.